Genome-Wide Association Study of Tacrolimus Pharmacokinetics Identifies Novel Single Nucleotide Polymorphisms in the Convalescence and Stabilization Periods of Post-transplant Liver Function - Liu, Yuan; Zhang, Chengdong; Li, Lei; Ou, Baochi; Yuan, Liyun; Zhang, Tao; Fan, Junwei; Peng, Zhihai (Frontiers in Genetics, 2019)
The liver function of the patients after liver transplantation (LT) is gradually restored, which is divided into convalescence period (CP) and stabilizing period (SP). The tacrolimus (TAC) variability explained by genetics and clinical factors in two periods were different. To explore tacrolimus (TAC) metabolism and establish models explaining TAC trough concentration variation inter-individuals in CP and SP respectively, we conducted the retrospective, single-center, discovery study, including 115 paired patients (115 donors and matched 115 recipients) who had LT. Donors and recipients were genotyped by Genome-wide analyzing (GWAS) using exome Chip; the CYP3A5 genotype was chose from Drug Metabolizing Enzymes and Transporters (DMET). Two novel exons (rs1927321, rs1057192) in donors were identified influencing TAC trough concentration in CP, and three novel exons (rs2667662, rs7980521, rs4903096) in donors and two (rs7828796, rs776746) in recipients in SP. Genetic factors played a crucial role in TAC metabolism, accounting for 44.8% in SP, which was higher than published papers before. Besides, well-known CYP3A5 just influenced TAC pharmacokinetics in SP.